PENGARUH GAYA MENGAJAR RESIPROKAL TERHADAP HASIL MENENDANG BOLA DALAM PERMAINAN SEPAK BOLA PADA SISWA PUTRA KELAS VII SMPN 1 GERUNG LOMBOK BARAT - Saputra, Sylvana Yaka; Suarti, Ni Ketut Alit; isnaini, Isnaini - (Universitas Hamzanwadi, 2019)
This study aims to determine the effect of reciprocal teaching styles on the results of kicking the ball in the game of soccer in seventh grade male students of Gerung 1 Junior High School, West Lombok. This study used the experimental method with a pre-experimental design, one group pretest-posttest design. The population in this study were seventh grade male students of Gerung 1Junior High School West Lombok 1, and the sample in this study were seventh grade male students of Gerung 1 junior high school West Lombok 1, totaling 31 people taken by proportional random sampling technique. The technique of collecting data is by using an action test to find out the results of kicking a ball in a soccer game. Data analysis using the t test, namely the formula t test and obtained tcount> t table. (5,648> 2042). Thus it can be concluded that there is an influence of reciprocal teaching style on the results of kicking the ball in the game of football in seventh grade male students of Gerung 1 Junior High School, West Lombok